(3GdEaGOI Ydi ePgH GdgGQhfi GdRjOis - (3CHh GdbGSe GdMSjf Hf GdMSjf GdghSej GdeDjOjs
(3ChdgG (B:s
(3HYO GdHSedI cJGH GdWgGQI HGH GdejGg dGjLhR GdWgGQI HeGA GdhQO hTHgI eeG cGf eYJUQkG ef TF s
(3BNQgG (B:s
(3BNQ aUd ai GdJhHI hef Ydjg eXGde EPG JGH YfO MVhQ GdehJ hde jLO ef jhUi Gdjg HbVGFgG cGf fGLjkG YfO Gddg s
(3HgG fXGe GdJYbjHIs
(3hGdGSe GdPi Ydi GdHWGbI NWC hgh Ydi ePgH GdSjO GdeDjO HGddg CMeO Hf GdMSjf GdgGQhfis
(3Z es
(3fSNI KGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3eJaQbGJs